2007
DOI: 10.1002/cvde.200606577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of Bis(2‐dimethylaminoethyl)amine Adducts of Strontium Bis(2,2,6,6‐tetramethylheptane‐3,5‐dionate) and Their Use in the CVD of Cubic Strontium‐Doped Hafnium Dioxides

Abstract: Monomeric, eight-coordinate Sr(tmhd) 2 [HN(CH 2 CH 2 NMe 2 ) 2 ](EtOH) (1), where tmhd is 2,2,6,6-tetramethylheptane-3,5-dionato, is synthesized from the reactions of HN(CH 2 CH 2 NMe 2 ) 2 , H-tmhd, and Sr(OEt) 2 (EtOH) 4 . Heating compound 1 at 130°C dissociates EtOH to form monomeric, seven-coordinate Sr(tmhd) 2 [HN(CH 2 CH 2 NMe 2 ) 2 ] (2). A combination of thermogravimetric analysis (TGA) and thermal stability tests establishes that compound 2 is stable at temperatures below 220°C. In a cold-wall, low-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The TG curve of precursor showed significant weight loss with an endothermic peak on the DTA curve at 150–180 °C. The residues of 3.2% indicated that thermal decomposition occurred with concomitant of neutral ligand dissociation from the indium complex, and similar decomposition patterns were reported . To determine the optimum dose of indium precursor for the self-limiting reaction, indium oxide films were deposited on a Si(100) substrate with increasing precursor amounts and reactant pulsing times at a temperature of 200 °C (Figure c).…”
Section: Resultssupporting
confidence: 58%
“…The TG curve of precursor showed significant weight loss with an endothermic peak on the DTA curve at 150–180 °C. The residues of 3.2% indicated that thermal decomposition occurred with concomitant of neutral ligand dissociation from the indium complex, and similar decomposition patterns were reported . To determine the optimum dose of indium precursor for the self-limiting reaction, indium oxide films were deposited on a Si(100) substrate with increasing precursor amounts and reactant pulsing times at a temperature of 200 °C (Figure c).…”
Section: Resultssupporting
confidence: 58%
“…6,7 One solution for obtaining the higher permittivity phases is to incorporate small amounts ͑Ͻ20 atom %͒ of other elements into the host HfO 2 film. 8 HfO 2 has been doped with Si, 9 Al, 10 N, 11 Sr, 12 Gd, and Er, 13 as well as Dy, 13,14 Sc, 14 and Y. 15,16 For example, permittivity values of over 25 have been reported for sputtered yttrium-doped HfO 2 ͑HfO 2 :Y͒ films with low yttrium content of 4 atom %.…”
mentioning
confidence: 97%
“…CVD of strontium-doped cubic HfO 2 layers was carried out using as precursors the liquid hepta-coordinated amine adduct [Sr(thd) 2 (tmdta)] (5, tmdta = NH(CH 2 CH 2 NMe 2 ) 2 ) in combination with [Hf(OBu-t) 4 ], in a cold-wall low-pressure reactor at 115-175 ∘ C. Scheme 1 shows the synthesis of 5, which was derived from the intermediate solvate by the elimination of EtOH at 130 ∘ C. The high-dielectric strontium hafnium oxide films have Sr/(Sr + Hf) atomic ratios of 0-0.83 26 …”
Section: Group 2 Elements (Mg Ca Sr Ba)mentioning
confidence: 99%